Effect of a wound healing protocol on patients with stage III and IV pressure ulcers: a preliminary observational study. (2nd April 2022) - Monaco, Dario; Zaghini, Francesco; Fiorini, Jacopo; Venturini, Giulia; Iovino, Paolo; Vellone, Ercole; Alvaro, Rosaria; Sili, Alessandro
Abstract : Objective: To evaluate the influence of a wound healing protocol for stage III and IV pressure ulcers (PUs), and to determine the predictive power of specific sociodemographic and clinical characteristics on wound healing and infection. Method: This longitudinal study included participants with stage III and IV PUs who were recruited from 10 acute care settings of an Italian university hospital, and who were managed with a protocol inspired by the TIMECare model. Data were collected between October 2018 and March 2019. The National Pressure Ulcer Advisory Panel Staging System was used to stage the PUs. Wound healing was assessed with the Pressure Ulcer Scale for Healing (PUSH). Nutritional status was assessed with the Mini Nutritional Assessment Index. Data collection took place at admission and every seven days thereafter—a total of six times before discharge. The outcome and predictors of wound healing were assessed with Student's paired t-tests and multiple linear regressions, respectively. Results: Patients (n=126) were almost equally split between male and female, with a mean age of 78.17 years and who were all retired. Stage III and IV PUs were most prevalent at the sacrum (65.5% and 73.2%, respectively). PUSH wound healing scores improved significantly after six weeks in both stage III and IV PUs (p<0.001). Nutritional status was predictive of wound healing (R 2 =0.12). Conclusion: Our results showed that a good nutritional status and a protocol inspired by the TIMECare model were associated with wound healing improvements in stage III and IV PUs. We recommend this protocol in older patients with stage III and IV PUs.